2000
DOI: 10.1002/etc.5620191008
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the test volume on the lag phase in biodegradation studies

Abstract: Abstract-Increasing the total volume of test medium resulted in decreased lag times (T L ) in biodegradability shake flask batch tests conducted with either surface water or with synthetic mineral medium inoculated with supernatant from settled activated sludge. Experiments were performed with test volumes ranging from 1.8 ml to 100 L using two 14 C-labeled model chemicals, 2,4-dichlorophenoxyacetic acid (2,4-D) and p-nitrophenol (PNP), both of which are known to be readily degradable after variable lag phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Although the physical and chemical test conditions which can affect biodegradation (Leahy and Colwell, 1990) are largely standardized in tests such as the OECD test series (OECD 301, 1992;OECD 303, 2001;OECD 306, 1992;OECD 309, 2004), the biological conditions of the inoculum is poorly defined and variable with respect to cell density, species, origin and history of the sample (Kowalczyk et al, 2015;Thouand et al, 2011). Pre-exposure to the tested chemical or similar chemical structures has been seen to enhance degradation by adaptation of the microbial community (Bauer and Capone, 1988;Leahy and Colwell, 1990;Marchal et al, 2003), and lag phases have been seen to depend on cell density in tests (Caparello and Larock, 1975), pre-adaptation of inoculum (Toräng and Nyholm, 2005) and total amount 4 of specifically degrading bacteria (Ingerslev et al, 2000). Previous studies reported the difference in biodegraded percentages of gasoline, diesel oil, crude oil and kerosene in soil samples (Hamamura et al, 2013;Marchal et al, 2003), hexadecane in surface water samples (Caparello and Larock, 1975), crude oil constituents in sea water (Kristensen et al, 2015), diesel and lubricating oil in sediments (Powell et al, 2007) and selected hydrocarbons in water-sediment mixtures from lakes (Cooney et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although the physical and chemical test conditions which can affect biodegradation (Leahy and Colwell, 1990) are largely standardized in tests such as the OECD test series (OECD 301, 1992;OECD 303, 2001;OECD 306, 1992;OECD 309, 2004), the biological conditions of the inoculum is poorly defined and variable with respect to cell density, species, origin and history of the sample (Kowalczyk et al, 2015;Thouand et al, 2011). Pre-exposure to the tested chemical or similar chemical structures has been seen to enhance degradation by adaptation of the microbial community (Bauer and Capone, 1988;Leahy and Colwell, 1990;Marchal et al, 2003), and lag phases have been seen to depend on cell density in tests (Caparello and Larock, 1975), pre-adaptation of inoculum (Toräng and Nyholm, 2005) and total amount 4 of specifically degrading bacteria (Ingerslev et al, 2000). Previous studies reported the difference in biodegraded percentages of gasoline, diesel oil, crude oil and kerosene in soil samples (Hamamura et al, 2013;Marchal et al, 2003), hexadecane in surface water samples (Caparello and Larock, 1975), crude oil constituents in sea water (Kristensen et al, 2015), diesel and lubricating oil in sediments (Powell et al, 2007) and selected hydrocarbons in water-sediment mixtures from lakes (Cooney et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The test volume of Respicond® is relatively low (150 mL) but remains compatible with the majority of biodegradation tests (Ingerslev et al 2000). This test volume may lead to an underestimation of the results due to the lower representativeness of bacterial inoculum sampling, with 4.425 mg of dry matter for 150 mL as compared to 29.5 mg for a test volume of 1 L (Blok and Booy 1984).…”
Section: Discussionmentioning
confidence: 97%
“…Working on improving test solution preparations for poorly water-soluble substances is a potentially interesting approach, since a genuinely realistic approach—i.e., performing tests at the likely environmentally relevant chemical concentration of a few parts per billion (10 −9  g/g)—is experimentally infeasible without the use of radiolabeled material. Many scientists have worked on this research subject (Gerike 1984; Blok et al 1985; Thomas et al 1986; De Morsier et al 1987; Nyholm 1990; Ramade 1995; Painter 1995 ; Handley et al 2002; Ingerslev et al 2000; Dumont et al 2006; Van Ginkel et al 2008; Li and Chen 2009; Rodrigues et al 2013). The most interesting test solution preparation methods described are sonication, adsorption onto solid supports (Nyholm 1990; Ramade 1995; Handley et al 2002; Li and Chen 2009; Rodrigues et al 2013), dispersion with emulsifier or solvent, dispersion with silicone oil (Dumont et al 2006; Van Ginkel et al 2008), or dispersion with emulsifier and silicone oil.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that increases in the medium volume accelerated biodegradation of the test chemicals. Ingerslev et al 37) also observed this tendency, from the viewpoint of lag phase, by changing test medium volume from 1.8 mL to 100 L with 4 mg/L of p-nitrophenol (PNP), reflecting the waiting time to begin preferential growth of specific degraders. By using water collected from a polluted river in Denmark, they found that increasing the total volume of the test medium resulted in decreased lag phases, and the phases were more constant above 180 mL of test medium.…”
Section: Influence On Biodegradation By Changing the Test Mediummentioning
confidence: 89%